A constituição da identidade na pós-modernidade: o simulacro da realidade - Oliveira, Fernando Maluf Dib (2016)
This work aims to analyse how the identity is constituted in the post modern era, a period in which a crisis in the formation of the identity takes place if compared to the modern period. The subject of the present investigation concerns the rising and development of modernity, since the projections for the social and cultural development failed giving opportunities to the appearance of post modernity. The social identity presents itself as a result of the social and cultural development according to Norbert Elias and Stuart Hall. The appearance and unfolding of modernity and its main features along with how these features influences the constitution of identity and the rising of the subject are approached based upon Alain Tourraine and Zygmunt Bauman’s theoretical work. It is this subject who no longer presents a fixed constitution of the identity during the post modernity since the subject is constantly exposed to the propaganda and to the media in a play of seduction and adequacy. At this point in the post modernism development – as a logic of the cultural development of this period – consumption culture is more and more determinant turning out to be a simulacrum and presenting a possibility of a hyper-reality. I used as an illustrative element of my theoretical discussion the movie Her (2013) to demonstrate the possible relationship between the simulacrum and the human being in contemporary societies, such unfolding has as its main authors Frederic Jameson and Jean Baudrillard whose contributions also features in this dissertation.